2021
DOI: 10.1002/qre.3041
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of exponentially weighted moving average control charts for monitoring the variability of log‐normal processes with estimated parameters

Abstract: In statistical process control (SPC), the control chart is a quite popular technique to monitor the process efficacy. From a statistical point of view, the control chart is considered superior if it has an effective structure withholding property of the resistance against infrequent situations in a practical environment. The current study is designed for the same purpose for observing the dispersion parameter of log‐normal distribution by using the structure of an exponentially weighted moving average (EWMA) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Their findings indicated that the proposed S-chart exhibited superior performance as compared to alternative methods. Akhtar et al 20 developed an EWMA chart customized for the lognormal process. Iqbal et al 21 introduced a control chart for monitoring the process mean and variability under the Bayesian Approach.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings indicated that the proposed S-chart exhibited superior performance as compared to alternative methods. Akhtar et al 20 developed an EWMA chart customized for the lognormal process. Iqbal et al 21 introduced a control chart for monitoring the process mean and variability under the Bayesian Approach.…”
Section: Introductionmentioning
confidence: 99%
“…A double generally weighted moving average (GWMA) control chart for monitoring dispersion parameters was designed by Alevizakos et al [25]. Akhtar et al [26] evaluated the EWMA control chart by using log-normal distributions with estimated parameters to monitor process variability. A GWMA maximum chart for joint monitoring was designed by Chatterjee et al [27].…”
Section: Introductionmentioning
confidence: 99%
“…Shaheen et al [23] developed a control chart for monitoring the lognormal process variation using repetitive sampling. Akhtar et al [24] designed an exponentially weighted moving average (EWMA) chart for the lognormal process. In this study, we discuss three S-charts, which include the Shewhart S-chart, the MAD control chart, and the lognormal S control chart, on the AARL and SDARL performance.…”
Section: Introductionmentioning
confidence: 99%